Implementation of Al-Qur'an Literacy in Community Character Development In Medan Senembah Village, Tanjung Morawa Sub-District - Sitti Isni Azzaah; Ali Imran Sinaga; Sapri Sapri (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The background for the formation of Al-Qur'an literacy activities in character building in the village of Medan Senembah, Tanjung Morawa District, namely as one of the government's programs regarding Al-Qur'an literacy culture, due to the low reading and writing of the Qur'an in society and the background of Vision and mission of the village head so that a religious village can be realized. This study aims to, 1) find out the background of the formation of Al-Qur'an literacy activities, 2) find out how the implementation of Al-Qur'an literacy in building community character, 3) find out how the impact of implementing Al-Qur'an literacy, 4) find out what are the supporting and inhibiting factors as well as solutions for implementing Al-Qur'an literacy in building community character. This research is a type of qualitative research with descriptive methods. Data analysis techniques were carried out in this study by collecting data, reducing data, presenting data and drawing conclusions. The results of this study indicate that the background to the formation of Al-Qur'an literacy activities in character building in the village of Medan Senembah, Tanjung Morawa District, is because of the government's program regarding Al-Qur'an literacy culture, the low reading and writing of the Qur'an in society and against the background of the village head's vision and mission to make a religious village, the implementation of Al-Qur'an literacy activities is carried out by planning, implementing, and evaluating during carrying out these activities. While the impact resulting from Al-Qur'an literacy activities in building the character of this community is that it can make people who are religious, diligently read the Al-Qur'an, have a responsible attitude, discipline, and tolerance. Supporting factors for Al-Qur'an literacy activities are from community support and facilities and infrastructure, the inhibiting factors are environmental factors, heredity and unfavorable weather. So the solution is to provide motivation and reward to the community so that more and more people love the Qur'an.